2000
DOI: 10.1093/bja/85.3.407
|View full text |Cite
|
Sign up to set email alerts
|

Continuous propofol anaesthesia for patients with myotonic dystrophy

Abstract: Myotonic dystrophy, a rare genetic disorder, may pose a serious problem to the anaesthesiologist due to muscular and extramuscular involvement. Thirteen patients, median age 21 yr were anaesthetized by continuous propofol infusion, fentanyl, atracurium and N2O to evaluate this combination in myotonic dystrophy. Intraoperatively, neither exaggerated reactions nor haemodynamic instability was observed. Recovery was smooth and quick. Although there was a significant decrease in mean postoperative vital capacity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 22 publications
0
27
0
2
Order By: Relevance
“…Tzabar et al [2] reported prolonged recovery time from propofol anesthesia; however, a high target concentration (6 mg ml -1 ) during surgery might be the reason for delayed recovery. Other reports [4,5] showed rapid emergence from anesthesia from continuous propofol infusion.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Tzabar et al [2] reported prolonged recovery time from propofol anesthesia; however, a high target concentration (6 mg ml -1 ) during surgery might be the reason for delayed recovery. Other reports [4,5] showed rapid emergence from anesthesia from continuous propofol infusion.…”
Section: Discussionmentioning
confidence: 90%
“…In some reports, propofol had been successfully used [4,5]. However, other reports suggested prolonged recovery [2], exaggerated physiologic responses [3], and myotonia [6].…”
Section: Discussionmentioning
confidence: 99%
“…Propofol has been used in patients with myotonia with variable responses, including prolonged recovery, altered dose-response curves, precipitation of myotonias and uneventful administration. [78] Considering this we used propofol for induction only and not for maintenance of anaesthesia. As our patient had absence of cardiovascular system involvement, we used desflurane for the maintenance of anaesthesia and it provided good control over anaesthetic depth as well as haemodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…PSA agents such as propofol, narcotics, benzodiazepines, and ketamine all have case reports describing their successful use in children with unusual inborn errors of metabolism. [75][76][77][78][79][80][81][82][83][84] Metabolism or excretion of any sedation or analgesia agent may be prolonged in children with liver or kidney problems. These effects do not impact the initial dosing of a sedative or narcotic, only the timing and amount of subsequent doses.…”
Section: Endocrine/metabolic Problemsmentioning
confidence: 99%